Performance analysis of LMS based control algorithm for power quality improvement in three phase grid connected system for linear/non-linear load - Ahmad, Mohmmad; Kirmani, Sheeraz (Institute of Advanced Engineering and Science, 2019)
This paper presents the adaptive filtering based least mean square control algorithm for distribution static compensator (DSTATCOM) in three-phase grid tied system for linear/non-linear load, to solve the power quality problems caused by solid-state equipment and devices. This is shown that the active component weights obtained from the load currents in the LMS adaptive filter are used to produce the reference currents and subsequently produces the switching pulses for VSC of the compensator. The complete circuit along with the adaptive technique and diode bridge rectifier type nonlinear load is simulated in Matlab/Simulink software. Initially the circuit was simulated for a three phase linear inductive load. Later it was simulated for a rectifier load connected at PCC with a disconnection of the load of any phase for a short duration of time. It is concluded that the harmonics are found within the limit. The harmonics and power results for both types of loads are compared in a tabular form. Hence this three phase system with DSTATCOM improves the power quality in the three-phase distribution network therefore, serves to provide harmonics reduction, load balancing and regulating the terminal voltage at the point of common coupling (PCC).